Asuhan Kebidanan pada Balita dengan Gizi Kurang di Wilayah Kayon Kota Palangkaraya - Diya Andriani; Ika Mardiatul Ulfa; Harta Harta (Jurnal Pakar Kesehatan, 2026)
Malnutrition remains a major health issue among toddlers in Indonesia, including in the Puskesmas Kayon area of Palangka Raya City, as it can hinder growth and development and increase the risk of illness. Factors contributing to this condition include inappropriate feeding practices, low maternal nutritional knowledge, and family socioeconomic limitations, making midwifery care essential through education, growth monitoring, and parental support. This case study aimed to describe the midwifery care provided to a 24-month-old toddler with malnutrition, with data collected through interviews, observations, physical examinations, and documentation using growth and development assessment tools, analyzed using the SOAP approach. The child initially weighed 9.5 kg, had a height of 75 cm, and an upper-arm circumference of 13 cm, indicating malnutrition. After three home visits involving education on balanced nutrition, meal-schedule arrangement, and emotional support for the mother, the toddler’s weight increased to 11.3 kg, and appetite improved. Appropriate midwifery care, combined with strong family involvement, proved effective in improving the toddler’s nutritional status.